Composting process by using palm oil mill effluent (POME) aerobic sludge, decanter cake and rice husk ASH - Nur Ezyan, Badrul Hisham (2020)
Palm oil mill industry had contributed to significant pollution especially river pollution when they discharged their effluents such as POME sludge and decanter cake into the rivers. To solve the environmental problem, these wastes can be utilized as fertilizer through composting process. However, there are some drawbacks in which possibly occur in composting process such as time consuming and the quality of compost. In order to facilitate the composting process, it was suggested to use rice husk ashes as additional raw materials due to its physical and chemical properties. The objectives of this work are to characterize the physical and chemical properties of raw materials (POME aerobic sludge, decanter cake, rice husk ash), to formulate the organic compost at different rice husk ash composition, to observe the heating effect towards the composting process and to compare the physicochemical properties of formulated compost with existing commercial product. In this work, POME aerobic sludge and decanter cake were mixed at constant weight ratio of (1:1) with addition of different amount of rice husk ashes. Then, the composting processes were carried out in 50 days by using compost bins. During the composting process, temperature and pH profile of compost were monitored daily. After composting process completed, the matured compost was analysed in terms of elemental analysis, pH, moisture content and water holding capacity. The result indicates that rice husk ash composition at 6.98% gives significant results in the compost formulation as the moisture content maintain within the range of 50-60% and range of 61-73% for water holding capacity. At the end of composting, sample with 6.98% rice husk ash obtain pH of 6.44, C/N ratio of 10.28 and N-P-K ratio of 3.3-8.1-9.7. The results obtain from this study were used for subsequent study by using forced heating composter. Forced heating composter produced compost with lower moisture content and water holding capacity compared to compost bin. However, composting by using both methods did not give significant difference in terms of chemical properties (macronutrients and micronutrients).